Do Strict Land Use Regulations Make Metropolitan Areas More Segregated by Income?. Issue 1 (2nd January 2016) - Lens, Michael C.; Monkkonen, Paavo
Abstract : Problem, research strategy, and findings: Income segregation has risen in each of the last four decades in U.S. metropolitan areas, which can have lifelong impacts on the health, economic productivity, and behaviors of residents. Although it is widely assumed that local land use regulations—such as minimum lot sizes and growth controls—exclude low-income households from wealthier neighborhoods, the empirical research is surprisingly limited. We examine the relationship between land use regulation and segregation by income using new measures for the 95 biggest cities in the United States. We find that density restrictions are associated with the segregation of the wealthy and middle income, but not the poor. We also find that more local pressure to regulate land use is linked to higher rates of income segregation, but that more state control is connected to lower-income segregation. Takeaway for practice: Density restrictions do drive urban income segregation of the rich, not the poor, but should be addressed because rich enclaves create significant metropolitan problems. Planners at the local level need assistance from regional and state efforts to ameliorate income segregation. Inclusionary housing requirements have a greater potential to reduce income segregation than bringing higher-income households into lower-income parts of the city. Finally, comprehensive and consistent data on the impacts of local land use regulations should be collected to inform future research and planning practice.